Tit Banking Socialization and Donation to Thfidzul Qur'an Orphanage An-Nnurriyyah Tambun Bekasi - Jana Sandra Sandra; Ade Suryana; Yuliawan Yuliawan; Sunarmin Sunarmin (Mau`izhah : Jurnal Kajian Keislaman, 2022)
Participating in social activities is a form of community service for a lecturer. With this participation, it is hoped that it will provide direct benefits to the community. This activity aims to provide financial literacy, especially an understanding of banking and other financial institutions for santri and female students at the Tahfidzul Qur'an An-Nurriyyah orphanage located in Siluman village, Mangunjaya village, RT/RW 03/005, Tambun Selatan sub-district, Bekasi district. The method of this community service activity has several stages, the first time is conducting an initial survey and interviews with the leadership of the Tahfidzul Qur'an An-Nurriyyah orphanage, the next stage after obtaining approval from the leadership of the Tahfidzul Qur'an An-Nurriyyah orphanage, then a briefing on banking was held. It is hoped that with this knowledge of banking, the santri and female students of the Tahfidzul Qur'an An-Nurriyyah orphanage will understand more about banking transactions so that it is hoped that the students and female students will run smoothly in banking transactions so that they do not want to be deceived by others, considering the end -Lately there are many frauds under the guise of banking.